A randomized controlled trial to compare antibiotic prophylaxis in elective gynecological surgeries: Single dose of cefazolin versus single dose of cefazolin and tinidazole - Shivani Garg; Seema Chopra; Shalini Gainder; Rashmi Bagga; Nusrat Shafiq; Neelam Aggarwal (Tzu Chi Medical Journal)
Objectives: To evaluate if addition of an anti-anaerobic agent to standard drug-cefazolin for antimicrobial prophylaxis would further decrease postoperative infectious morbidity or not. This is relevant as most of the infections in gynecological surgeries are anaerobic but cefazolin does not protect against anaerobes. Materials and Methods: The study design was a parallel randomized controlled trial. Two hundred patients undergoing benign gynecological surgeries were divided into two groups of 100 each. Group A received 2 g cefazolin 30–60 min before incision and Group B received 2 g cefazolin 30–60 min and 1.6 g tinidazole 60–120 min before incision. The patients were followed for any infectious morbidity for 1 month postoperatively. The analysis was done separately for abdominal, laparoscopic, and vaginal surgeries. The analysis was also done for surgeries according to the wound category, i.e. clean and clean-contaminated. Results: The two groups were comparable for age and body mass index (BMI). The two groups were comparable for the factors affecting infectious morbidity such as duration of surgery, blood loss, blood transfusions, duration of hospital stay, and need for additional antibiotics. The postoperative infectious morbidity was analyzed in terms of fever, surgical site infection (SSI), and urinary tract infection (UTI). No patient in vaginal and laparoscopic groups suffered from infectious morbidity. In abdominal surgeries group, postoperative fever occurred in 6/74 (8.1%) and 11/74 patients (14.8%) in Groups A and B, respectively (P = 0.38). SSI occurred in 1/74 (1.3%) and 2/74 (2.7%) patients in Groups A and B, respectively (P = 1.0). UTI occurred in 5/74 patients (6.7%) and 2/74 patients (2.7%) in Groups A and B, respectively (P = 0.44). The data were also analyzed for infectious morbidity for clean and clean-contaminated wound categories, and the results were nonsignificant between both groups for each type of wound category (P > 0.05). Conclusion: Cefazolin alone is a sufficient antibiotic prophylaxis for benign gynecological procedures.